IMPROVING METACOGNITIVE SKILLS THROUGH SCHOOLOGY–BASED BLENDED LEARNING WITH SCIENTIFIC APPROACH - Rona Dea Meistasari; Utiya Azizah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This research aimed to describe the feasibility, the improvement of metacognitive skills, learning outcomes, and students' responses to schoology–based blended learning with a scientific approach on the topic of reaction rate. This research used a pre-experimental design, namely One Group Pretest-Postest Design. The research was conducted in class XI IPA 3 SMAN 1 Gurah involving 36 students without the control class. The data were collected through observation, test, and questionnaire. Then, the data were analyzed by calculating the percentage, mean, paired t-test, and N-Gain test. The results showed that 1) Schoology–based blended learning was carried out very well with the criteria of very good for 99.25%; 2) Metacognitive skills which was practiced through Schoology–based blended learning was scored 0.534 meaning that the skills improved well; 3) Student learning outcomes also experienced the completeness for 61% which stated that the use of Schoology–based blended learning was good to improve learning outcomes 4) The students’ response towards the use of Schoology–based blended learning as a learning innovation using technology was considered good with a percentage of 75%. Generally, Schoology–based blended learning was effective in improving students' metacognitive skills.